Sportsspektakler - Møller, Verner (Forum for Idræt, 2004)
Analyse af sporten i ’spektakelsamfundet’, som bl.a. konkluderer, at kommercialiseringen ikke i sig selv medfører et forfald inden for sporten. Sport as spectacle Over the years many pages have been written about the misery of sport, its corruption and imminent demise. It is quite true that sport and the conditions under which it operates change, but this is not synonymous with decay. On the contrary. This article demonstrates that sport has the effect of anchoring us in life and is, in fact, a civilising influence. By means of critical analyses of John J. MacAloon’s account of sport’s dimension as festival and Guy Debord’s analysis of the society of the spectacle, this article paves the way for an understanding of the fact that sport can in its essence be seen as popular culture’s substitute for the formative manifestations of high culture, and that commercialisation, which is often dragged out as the root of sport’s unhappy development, in reality is the motor driving sport forward as a developmental project in popular culture.